Appearance
โDetermine the result of subtracting 3 - 5i from 6 + 2i.
๐กFirst, I need to subtract the complex numbers (3 - 5i) from (6 + 2i).I'll start by subtracting the real parts of the two complex numbers: (6 - 3 = 3).Next, I'll subtract the imaginary parts: (2i - (-5i) = 2i + 5i = 7i).Finally, I'll combine the results of the real and imaginary parts to get the final answer: (3 + 7i).
โJessy starts with a jewelry box that has 10 necklaces, 15 earrings, 5 bracelets, and 8 rings. She goes to Store A and buys 10 more necklaces, 2/3 as many earrings as she initially had, and 3 more bracelets. Afterwards, she visits Store B, where she buys twice as many rings as she originally had, and 4 additional necklaces. After returning home, her mother gives her 1/5 times more earrings than the number she purchased at Store A. Calculate the total number of jewelry pieces Jessy has in her box if she puts all of them together.
๐กFirst, I will identify the initial number of each type of jewelry that Jessy has:- **Necklaces:** 10- **Earrings:** 15- **Bracelets:** 5- **Rings:** 8Next, I will calculate the purchases made at Store A:- **Necklaces:** 10 additional- **Earrings:** 2/3 of the initial 15, which is ( frac{2}{3} times 15 = 10 )- **Bracelets:** 3 additionalThen, I will determine the purchases made at Store B:- **Rings:** Twice the original amount, which is ( 2 times 8 = 16 )- **Necklaces:** 4 additionalAfter that, I will account for the gift from Jessy's mother:- **Earrings:** 1/5 of the number purchased at Store A, which is ( frac{1}{5} times 10 = 2 )Finally, I will sum up all the quantities for each type of jewelry:- **Necklaces:** ( 10 + 10 + 4 = 24 )- **Earrings:** ( 15 + 10 + 2 = 27 )- **Bracelets:** ( 5 + 3 = 8 )- **Rings:** ( 8 + 16 = 24 )Adding all these together gives the total number of jewelry pieces:( 24 + 27 + 8 + 24 = 83 )
โThe Quill and Scroll is a stationery shop. Its stock and sales for June are listed in the table shown. What percent of its sales were not pens, pencils, or erasers?begin{tabular}{|l|c|}multicolumn{2}{c}{}hlinetextbf{Item}&textbf{%~of June Sales}hlinePens&25hlinePencils&30hlineErasers&20hlineOther&?hlineend{tabular}
๐กFirst, I need to determine the total percentage of sales that were pens, pencils, and erasers. I add the percentages of pens, pencils, and erasers together:25% (pens) + 30% (pencils) + 20% (erasers) = 75%.Since the total percentage of all sales should add up to 100%, I subtract the combined percentage of pens, pencils, and erasers from 100% to find the percentage of other items:100% - 75% = 25%.Therefore, 25% of the sales were not pens, pencils, or erasers.
โa trader bought a car at 20 % discount on its original price . he sold it at a 70 % increase on the price he bought it . what percent of profit did he make on the original price ?
๐กFirst, I need to determine the price the trader paid for the car after a 20% discount. If the original price is ( P ), then the purchase price is ( 0.80P ).Next, the trader sold the car at a 70% increase on the purchase price. This means the selling price is ( 0.80P + 0.70 times 0.80P = 1.36P ).To find the profit percentage based on the original price, I calculate the difference between the selling price and the original price, which is ( 1.36P - P = 0.36P ).Finally, I determine the profit percentage by dividing the profit by the original price and multiplying by 100: ( frac{0.36P}{P} times 100% = 36% ).
โIf n diamondsuit m = n^2 m^3, what is frac{5 diamondsuit 3}{3 diamondsuit 5}?textbf{(A)} frac{1}{5}qquadtextbf{(B)} frac{2}{5}qquadtextbf{(C)} frac{3}{5}qquadtextbf{(D)} frac{4}{5}qquadtextbf{(E)} 1
๐กOkay, so I have this problem here: If ( n diamondsuit m = n^2 m^3 ), what is ( frac{5 diamondsuit 3}{3 diamondsuit 5} )? The answer choices are ( textbf{(A)} frac{1}{5} ), ( textbf{(B)} frac{2}{5} ), ( textbf{(C)} frac{3}{5} ), ( textbf{(D)} frac{4}{5} ), and ( textbf{(E)} 1 ). Hmm, let me try to figure this out step by step.First, I need to understand what the operation ( diamondsuit ) means. It's defined as ( n diamondsuit m = n^2 m^3 ). So, for any two numbers ( n ) and ( m ), the operation ( diamondsuit ) takes ( n ) squared and multiplies it by ( m ) cubed. Got it.Now, the problem is asking for the ratio of ( 5 diamondsuit 3 ) to ( 3 diamondsuit 5 ). That is, I need to compute ( frac{5 diamondsuit 3}{3 diamondsuit 5} ). Let me break this down.Let's start by calculating ( 5 diamondsuit 3 ). Using the definition of ( diamondsuit ), this should be ( 5^2 times 3^3 ). Calculating each part:- ( 5^2 = 25 )- ( 3^3 = 27 )So, ( 5 diamondsuit 3 = 25 times 27 ). Let me compute that: 25 times 27. Hmm, 25 times 20 is 500, and 25 times 7 is 175, so adding those together gives 500 + 175 = 675. So, ( 5 diamondsuit 3 = 675 ).Next, I need to calculate ( 3 diamondsuit 5 ). Again, using the definition, this is ( 3^2 times 5^3 ). Let's compute each part:- ( 3^2 = 9 )- ( 5^3 = 125 )So, ( 3 diamondsuit 5 = 9 times 125 ). Let me do that multiplication: 9 times 100 is 900, and 9 times 25 is 225, so adding those gives 900 + 225 = 1125. Therefore, ( 3 diamondsuit 5 = 1125 ).Now, I need to find the ratio of these two results: ( frac{675}{1125} ). Let me simplify this fraction. Both 675 and 1125 are divisible by 225, I think. Let me check:- 675 divided by 225 is 3.- 1125 divided by 225 is 5.So, ( frac{675}{1125} = frac{3}{5} ). Therefore, the ratio ( frac{5 diamondsuit 3}{3 diamondsuit 5} ) simplifies to ( frac{3}{5} ).Looking back at the answer choices, ( frac{3}{5} ) corresponds to option ( textbf{(C)} ). So, I think the correct answer is ( textbf{(C)} frac{3}{5} ).Wait, just to make sure I didn't make any calculation errors. Let me double-check my computations.For ( 5 diamondsuit 3 ):- ( 5^2 = 25 )- ( 3^3 = 27 )- ( 25 times 27 = 675 ) (Yes, that's correct.)For ( 3 diamondsuit 5 ):- ( 3^2 = 9 )- ( 5^3 = 125 )- ( 9 times 125 = 1125 ) (That's also correct.)Then, the ratio ( frac{675}{1125} ). Dividing numerator and denominator by 225:- ( 675 รท 225 = 3 )- ( 1125 รท 225 = 5 )- So, ( frac{3}{5} ) is indeed the simplified form.Alright, I feel confident that my answer is correct. It's always good to check, especially when dealing with exponents and multiplication, as it's easy to make a small mistake there.Another way to approach this problem might be to look for patterns or properties of the operation ( diamondsuit ) that could simplify the ratio without calculating each term separately. Let me see if that's possible.Given ( n diamondsuit m = n^2 m^3 ), then ( frac{n diamondsuit m}{m diamondsuit n} = frac{n^2 m^3}{m^2 n^3} ). Simplifying this, we can cancel out terms:- ( frac{n^2}{n^3} = frac{1}{n} )- ( frac{m^3}{m^2} = m )So, ( frac{n diamondsuit m}{m diamondsuit n} = frac{m}{n} ).Wait, that's interesting. So, in general, the ratio ( frac{n diamondsuit m}{m diamondsuit n} ) simplifies to ( frac{m}{n} ). Applying this to our specific case where ( n = 5 ) and ( m = 3 ), we get:( frac{5 diamondsuit 3}{3 diamondsuit 5} = frac{3}{5} ).That's the same result as before, but arrived at through a more general approach. This method might be quicker and less error-prone, especially if the numbers were larger or more complex.So, using this property, we can see that the ratio is simply ( frac{m}{n} ), which in this case is ( frac{3}{5} ). This confirms my earlier calculation.I think this is a solid approach. It's always nice when you can find a general formula or property that applies to a problem, as it can save time and reduce the chance of computational errors.In summary, whether I compute each term separately and then take the ratio or use the general property of the operation ( diamondsuit ), I arrive at the same answer: ( frac{3}{5} ). Therefore, I'm confident that the correct choice is ( textbf{(C)} frac{3}{5} ).**Final Answer**boxed{C}
โCalculate the lengths of the arcs of the curves given by equations in the rectangular coordinate system.y = -arccos(sqrt{x}) + sqrt{x - x^2}, quad 0 leq x leq frac{1}{4}
๐กOkay, so I have this problem where I need to find the length of the arc of the curve given by the equation ( y = -arccos(sqrt{x}) + sqrt{x - x^2} ) from ( x = 0 ) to ( x = frac{1}{4} ). Hmm, arc length. I remember that the formula for the arc length of a curve ( y = f(x) ) from ( x = a ) to ( x = b ) is:[L = int_{a}^{b} sqrt{1 + left( frac{dy}{dx} right)^2} , dx]So, first things first, I need to find the derivative of ( y ) with respect to ( x ). Let me write down the function again:[y = -arccos(sqrt{x}) + sqrt{x - x^2}]Alright, so I need to differentiate this function term by term. Let's start with the first term, ( -arccos(sqrt{x}) ). I remember that the derivative of ( arccos(u) ) with respect to ( x ) is ( -frac{u'}{sqrt{1 - u^2}} ). So, applying that here:Let ( u = sqrt{x} ), so ( u' = frac{1}{2sqrt{x}} ). Therefore, the derivative of ( -arccos(sqrt{x}) ) is:[-frac{d}{dx} arccos(sqrt{x}) = -left( -frac{1}{sqrt{1 - (sqrt{x})^2}} cdot frac{1}{2sqrt{x}} right) = frac{1}{2sqrt{x}sqrt{1 - x}}]Wait, hold on, I think I messed up the signs. The derivative of ( arccos(u) ) is ( -frac{u'}{sqrt{1 - u^2}} ), so since there's already a negative sign in front of ( arccos ), it should be:[-frac{d}{dx} arccos(sqrt{x}) = -left( -frac{1}{sqrt{1 - x}} cdot frac{1}{2sqrt{x}} right) = frac{1}{2sqrt{x}sqrt{1 - x}}]Yes, that seems right.Now, moving on to the second term, ( sqrt{x - x^2} ). Let me set ( v = x - x^2 ), so ( v' = 1 - 2x ). The derivative of ( sqrt{v} ) is ( frac{v'}{2sqrt{v}} ), so:[frac{d}{dx} sqrt{x - x^2} = frac{1 - 2x}{2sqrt{x - x^2}}]Okay, so putting it all together, the derivative ( frac{dy}{dx} ) is:[frac{dy}{dx} = frac{1}{2sqrt{x}sqrt{1 - x}} + frac{1 - 2x}{2sqrt{x - x^2}}]Hmm, let me see if I can simplify this expression. Notice that ( sqrt{x - x^2} = sqrt{x(1 - x)} ), so ( sqrt{x - x^2} = sqrt{x}sqrt{1 - x} ). Therefore, the second term becomes:[frac{1 - 2x}{2sqrt{x}sqrt{1 - x}}]So now, both terms have the same denominator, ( 2sqrt{x}sqrt{1 - x} ). Let me write them together:[frac{dy}{dx} = frac{1}{2sqrt{x}sqrt{1 - x}} + frac{1 - 2x}{2sqrt{x}sqrt{1 - x}} = frac{1 + (1 - 2x)}{2sqrt{x}sqrt{1 - x}} = frac{2 - 2x}{2sqrt{x}sqrt{1 - x}} = frac{1 - x}{sqrt{x}sqrt{1 - x}}]Simplifying further, ( frac{1 - x}{sqrt{x}sqrt{1 - x}} = sqrt{frac{1 - x}{x}} ). So, the derivative simplifies to:[frac{dy}{dx} = sqrt{frac{1 - x}{x}}]Alright, that seems manageable. Now, plugging this into the arc length formula:[L = int_{0}^{frac{1}{4}} sqrt{1 + left( sqrt{frac{1 - x}{x}} right)^2} , dx]Let me compute the expression inside the square root:[1 + left( sqrt{frac{1 - x}{x}} right)^2 = 1 + frac{1 - x}{x} = frac{x + 1 - x}{x} = frac{1}{x}]So, the integrand simplifies to:[sqrt{frac{1}{x}} = frac{1}{sqrt{x}}]Therefore, the arc length integral becomes:[L = int_{0}^{frac{1}{4}} frac{1}{sqrt{x}} , dx]This is a standard integral. The integral of ( frac{1}{sqrt{x}} ) is ( 2sqrt{x} ). So, evaluating from 0 to ( frac{1}{4} ):[L = left[ 2sqrt{x} right]_{0}^{frac{1}{4}} = 2sqrt{frac{1}{4}} - 2sqrt{0} = 2 cdot frac{1}{2} - 0 = 1]Wait, so the arc length is 1? That seems surprisingly simple. Let me double-check my steps.First, the derivative calculation: I started with ( y = -arccos(sqrt{x}) + sqrt{x - x^2} ). The derivative of ( -arccos(sqrt{x}) ) is ( frac{1}{2sqrt{x}sqrt{1 - x}} ), and the derivative of ( sqrt{x - x^2} ) is ( frac{1 - 2x}{2sqrt{x - x^2}} ). Combining these gives ( sqrt{frac{1 - x}{x}} ). That seems correct.Then, plugging into the arc length formula, I got ( sqrt{1 + left( sqrt{frac{1 - x}{x}} right)^2} = sqrt{frac{1}{x}} ). That also seems right because ( 1 + frac{1 - x}{x} = frac{x + 1 - x}{x} = frac{1}{x} ).So, integrating ( frac{1}{sqrt{x}} ) from 0 to ( frac{1}{4} ) gives 1. Hmm, okay, maybe it is correct. The function simplifies nicely, so the arc length ends up being 1.I guess I was expecting something more complicated, but sometimes things cancel out nicely. I don't see any mistakes in my calculations, so I think the arc length is indeed 1.